Clinical Evaluation of a Novel Stool Antigen Test Using Bioluminescent Enzyme Immunoassay for Detecting Helicobacter pylori. (21st April 2022) - Kakiuchi, Toshihiko; Matsuo, Muneaki; Sakata, Yasuhisa; Fujimoto, Kazuma
Abstract : Background . BLEIA ™ "EIKEN" Helicobacter pylori antigen (B[EIA]) is based on the bioluminescent enzyme immunoassay (BLEIA) method that was newly developed with high sensitivity in detecting Helicobacter pylori ( H. pylori ) antigen in feces. Methods . In the project for H. pylori screening and treatment in Saga Prefecture in 2019, 141 students received the stool H. pylori antigen test as a secondary test. For 141 students, a comparative test was conducted between B (EIA) and extracorporeal diagnostic agents that were marketed in Japan as of 2019. The detection performance of H. pylori ATCC43504 standard strain and H. pylori antigen in commercial human fecal specimens were conducted. Results . The comparison of B (EIA) with Quick Chaser TM H. pylori (Q [IC]) revealed positive and negative concordance ratios of B (EIA) to Q (IC) of 100.0% (110/110) and 71.0% (22/31), respectively. A comparative test was conducted between B (EIA) and extracorporeal diagnostic agents that were marketed in Japan as of 2019, and B (EIA) was most sensitive on "detecting H. pylori antigen of ATCC43504 standard strain" and "detecting H. pylori antigen in commercial human fecal specimens, " compared with other kits. Nine dissociated specimens that were negative for Q (IC) and positive for B (EIA) were confirmed. The measured value of B (EIA) in the dissociation samples were 1.3–87.4 cutoff index in the range that can be evaluated as negative by other fecal H. pylori antigen test kits, all the dissociation samples were H. pylori antigen-positive cases, and finally the cause of result divergence was presumed as false negative due to insufficient sensitivity of Q (IC). Conclusion . B (EIA) that is based on the BLEIA method, which applies firefly luciferase luminescence, is more sensitive than stool antigen test kits that are currently marketed in Japan and is very useful in diagnosing H. pylori infection, especially in situations where noninvasive tests are preferred, such as in children.